Epigenetic Regulation of Memory-Therapeutic Potential for Disorders - Singh, Padmanabh (Curr Neuropharmacol, 2017)
BACKGROUND: Memory is a vital function which declines in different physiological and pathological conditions such as aging and neurodegenerative diseases. Research in the past has reported that memory formation and consolidation require the precise expression of synaptic plasticity genes. However, little is known about the regulation of these genes. Epigenetic modification is now a well established mechanism that regulates synaptic plasticity genes and neuronal functions including memory. Therefore, we have reviewed the epigenetic regulation of memory and its therapeutic potential for memory dysfunction during aging and neurological disorders. METHOD: Research reports and online contents relevant to epigenetic regulation of memory during physiological and pathological conditions have been compiled and discussed. RESULTS: Epigenetic modifications include mainly DNA methylation and hydroxymethylation, histone acetylation and methylation which involve chromatin modifying enzymes. These epigenetic marks change during memory formation and impairment due to dementia, aging and neuro- degeneration. As the epigenetic modifications are reversible, they can be modulated by enzyme inhibitors leading to the recovery of memory. CONCLUSION: Epigenetic modifications could be exploited as a potential therapeutic target to recover memory disorders during aging and pathological conditions.